An Ecological Framework to Support Small-Scale Shared Housing for Persons with Neurocognitive Disorders of the Alzheimer's and Related Types: A Literature Review - Kevin N. Bortnick (SAGE Publishing, 2017)
Background: Small scale shared housing arrangements (SHAs) is a deinstitutionalized model of care designed to resemble a typical home of <10 people and are increasingly available for persons with neurocognitive disorders of the Alzheimer's and related types (NCD). However, there is little aggregate evidence of their effect on persons with NCD thus, a literature review was performed. Methods: Database searches were conducted across CINAHL Complete, OTseeker, PubMed, Ovid, Academic One File, ProQuest Nursing and Allied Health, the World Wide Web and Google Scholar using the several key words that included neurocognitive disorders, Alzheimer's, dementia, quality of life, well-being, occupational performance, activities of daily living, small scale shared housing, sheltered housing and group homes. Bibliographic references from final articles were also examined. Selection criteria involved three steps: screening perspective articles by title and abstract, assessing full text for eligibility and finally, reviewing full-texts. Results: 16 studies were selected for final review where most found the association of SHAs with various occupational performance indicators unique to the NCD population better than or equal to controls (traditional models of long term care). A small minority of studies had mixed or inconclusive results. No study found SHAs necessarily worse than controls. Conclusion: The SHA model has many benefits for person's with NCD and may be especially advantageous for those in the early stages of the disease process. The occupational therapy profession should continue to raise awareness of SHAs and consider ecological theory as a valid basis for their expansion.